Interpreting interviews - Alvesson, Mats, 1956- (London : SAGE Publications Ltd, 2023)
Through the use of eight original metaphors for understanding what may happen in interviews and what may guide the interviewee (more than telling the truth or revealing experiences), the reader is encouraged to do interviews in clever ways. This text enables you to question the interpretive nature and theoretical underpinnings of the interview method, and of the knowledge which is conveyed through it. The updated second edition includes new content on: (a) How to avoid traps in interviews; (b) How to use interviewees with experience and insight; (c) How to work creatively with generative material; (d) The value of repeat interviewing over time; (e) The importance of supplementing interviews with other methods; and (f) Possibilities of interview-based research accompanied by examples. This text is essential reading for upper undergraduate and postgraduate students of qualitative methods, and researchers looking to more clearly conceptualize their interviewing practice and explore its theoretical basis. Mats Alvesson is professor at University of Bath and is also affiliated with Lund University, Stockholm School of Economics and Bayes Business School.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Qualitative research -- Methodology